Apolipoprotein B Antisense Inhibition -Update on Mipomersen - Gebhard, Catherine; Huard, Gabriel; Kritikou, Ekaterini A.; Tardif, Jean-Claude (Current Pharmaceutical Design, 2013)
Dyslipidemia is one of the main risk factors leading to cardiovascular disease (CVD). The standard of therapy, administration of statins, in conjunction with lifestyle and habit changes, can improve high cholesterol levels in the majority of patients. However, some patients with familial hypercholesterolemia (FH) need low-density-lipoprotein cholesterol (LDL-C) apheresis, as the available medications fail to reduce LDL-C levels sufficiently even at maximum doses. Intense research on cholesterol reducing agents and rapid progress in drug design have yielded many approaches that reduce cholesterol absorption or inhibit its synthesis. Antisense oligonucleotides (ASOs) targeting the production of apolipoprotein B-100 (apoB-100), inhibitors of proprotein convertase subtilisin/kexin type 9, microsomal triglyceride transfer protein inhibitors, squalene synthase inhibitors, peroxisome proliferator-activated receptor agonists, and thyroid hormone receptor agonists are some of the evolving approaches for lipid-lowering therapies. We provide an overview of the apoB ASO approach and its potential role in the management of dyslipidemia. Mipomersen (ISIS- 301012, KYNAMRO™) is a synthetic ASO targeting the mRNA of apoB-100, which is an essential component of LDL particles and related atherogenic lipoproteins. ASOs bind to target mRNAs and induce their degradation thereby resulting in reduced levels of the corresponding protein levels. Mipomersen has been investigated in different indications including homozygous and heterozygous FH, as well as in high-risk hypercholesterolemic patients. Recent phase II and III clinical studies have shown a 25-47percnt; reduction in LDL-C levels in mipomersen-treated patients. If future studies continue to show such promising results, mipomersen would likely be a viable additional lipid-lowering therapy for high-risk populations.
Keywords: mipomersen